(untitled) (Simbiótica. Revista Eletrônica, 2024)
Based on Foucault and Han’s readings on the configurations of neoliberalism, this article seeks to investigate how the logic of the “Burnout Society” is incorporated in postgraduate students on a case study at the University Vila Velha/ES. From the application of questionnaires, focus groups and semi-structured interviews with students, we analyzed four categories that are linked to the emergence of the logic of the “Burnout Society”. In the “feelings of anxiety” category, students alternate between desire and fear of the suffering potentially caused by the postgraduate experience. In the “overlapping demands” category, the multiplicity of social roles played by students poses challenges for academic insertion. In “individualization of suffering”, the feeling of “failure” is taken as an attribute of the individual, with the mobilization of atomized strategies to deal with these challenges. The “academic performance” category analyzes the demand felt by students to produce.